Development of Quality Management Model in Realizing Quality School Through Leadership and School-Based Evaluation - Roni Indra; Aan Komariah; Diding Nurdin; Rahmat Fadhli (STAI Hubbulwathan Duri, 2023)
This study aimed to find a feasible quality management model for realizing quality schools through leadership and school-based evaluation, especially at the junior high school level. The research locations were in six Junior High Schools that implemented the Program Sekolah Penggerak (SMP Penggerak) Batch 1 in Batam City. The study used explanatory sequential mixed methods. The number of samples used was 178 teachers, including six principals. The data analysis technique used the weighted mean scores to measure the average tendency of respondents' answers and Pearson's correlation to measure the level of relationship between variables. Based on the research results, a feasible quality management model is implemented through the PDCA approach in the activities of mission alignment, involvement and empowerment, roles and responsibilities, digitalization in management work, ethical commitment, knowledge management, action for change, or the acronym MERDEKA. This model can improve school quality.